2010
DOI: 10.1007/s12640-010-9184-0
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Exposure of Rats to Pre- and Post-Natal Manganese Enhances Behavioral Impairments Produced by Perinatal 6-Hydroxydopamine

Abstract: Rats lesioned shortly after birth with 6-hydroxydopamine (6-OHDA; 134 μg icv) represent a near-ideal model of severe Parkinson's disease because of the near-total destruction of nigrostriatal dopaminergic fibers. The element manganese, an essential cofactor for many enzymatic reactions, itself in toxic amount, replicates some clinical features similar to those of Parkinson's disease. The aim of this study was to examine the effect of neonatal manganese exposure on 6-OHDA modeling of Parkinson's disease in rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
1
8
0
3
Order By: Relevance
“…The 60 and 134-lg doses of 6-OHDA were associated with depletions of striatal DA by 92 and 98%, respectively, at 2-months [respectively 909 and 253 vs. 11606 (control) ng/g tissue] (Nowak et al 2011). The same 6-OHDA treatment doses in rats exposed perinatally to manganese resulted in virtually the same magnitude of striatal DA depletion.…”
Section: Biogenic Amine Content Of Brainmentioning
confidence: 80%
See 2 more Smart Citations
“…The 60 and 134-lg doses of 6-OHDA were associated with depletions of striatal DA by 92 and 98%, respectively, at 2-months [respectively 909 and 253 vs. 11606 (control) ng/g tissue] (Nowak et al 2011). The same 6-OHDA treatment doses in rats exposed perinatally to manganese resulted in virtually the same magnitude of striatal DA depletion.…”
Section: Biogenic Amine Content Of Brainmentioning
confidence: 80%
“…However, in our latest study we demonstrated that ontogenetic exposure to manganese produced an enhancement of behavioral toxicity to a moderate dose of 6-OHDA (60 lg icv) despite the fact that there was no enhanced depletion of striatal DA depletion by manganese treatment (Nowak et al 2011).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…25) Recently, it was found that Mn augments the neurotoxic effect of 6-hydroxydopamine, a treatment used to model PD in animals. 26) We do not have data concerning the levels of Mn and Al in the LCa/Mg mice, but these previous results suggest that LCa/Mg in mice can lead to an indirect accumulation of Mn and Al in the brain with subsequent degeneration of DA neurons. We are conducting further experiments in order to elucidate the accumulation of Mn and Al in LCa/Mg mice.…”
Section: Discussionmentioning
confidence: 72%
“…Mn neurotoxicity has shown selectivity for DA neurons [22]. Recently, it was demonstrated that Mn augments the neurotoxic effect of 6-hydroxydopamine, a treatment used to model PD in animals [23]. Together, these results suggest that LCa/Mg in mice may lead to an indirect accumulation of Mn and Al in the brain with subsequent degeneration of DA neuron.…”
Section: Discussionmentioning
confidence: 99%